PENGGUNAAN KEMBALI BANGKAI BUS TRANSJAKARTA SEBAGAI MODUL PASAR PESING KONENG - Kristopher Henrico Ali; Franky Liauw (Jurusan Arsitektur dan Perencanaan, 2022)
Pesing Koneng Market is a wild market that has been operating in the Pesing area for a long time. In the past, the Pesing market managed to attract visitors from remote areas of Batavia. However, seeing its development which has given rise to various problems, Urban Acupuncture strategy is needed to respond the degradation that occurs. Like a hermit crab changing its shell, the Pesing Koneng market that grows beyond its